The Preemptive Analgesic Effect of Capsaicin Involves Attenuations of Epidermal Keratinocytes Proliferation and Expression of Pro-Inflammatory Mediators After Plantar Incision in Rats - Guo R; Qiu H; Li H; Ma D; Guan Y; Wang Y (Journal of Pain Research, 2023)
Ruijuan Guo,1 Huanrong Qiu,1 Huili Li,2 Danxu Ma,2 Yun Guan,3 Yun Wang2 1Department of Anesthesiology, Beijing Friendship Hospital, Capital Medical University, Beijing, 100050, People’s Republic of China; 2Department of Anesthesiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 3Department of Anesthesiology and Critical Care Medicine, The Johns Hopkins University School of Medicine, Baltimore, MD, 21205, USACorrespondence: Yun Wang, Department of Anesthesiology, Beijing Chaoyang Hospital, Capital Medical University, No. 8, Gongtinan Road, Chaoyang District, Beijing, 100020, People’s Republic of China, Tel +86-010-85231330, Fax +86-10-65077808, Email wangyun129@ccmu.edu.cnPurpose: Subcutaneous infiltration of capsaicin, which initially activates transient receptor potential vanilloid  1 (TRPV1) receptors, can subsequently desensitize TRPV1-expressing nociceptors and induce analgesia in different pain models. Yet, whether the modulation of keratinocytes may also contribute to the analgesic action of capsaicin treatment remains unclear. In a rat model of postoperative pain, we tested the hypothesis that subcutaneous injection of capsaicin inhibited the proliferation of epidermal keratinocytes and their expression of pronociceptive inflammatory mediators after plantar incision.Methods: The plantar incision model was carried out in the current study. Behavioral tests were used to evaluate postoperative pain-related behaviors in rats. Immunohistochemistry was used to investigate epidermal keratinocytes proliferation and expression of pro-inflammatory mediators in keratinocytes in rats.Results: Behaviorally, plantar incision induced robust postoperative pain hypersensitivity. However, subcutaneous pretreatment of capsaicin (1%) but not the vehicle, prevented the development of postoperative pain. There was an increased proliferation of keratinocytes and the expressions of interleukin-1β (IL-1β) and tumour necrosis factor-alpha (TNF-α) in keratinocytes at 3 d and 7 d after plantar incision. However, these changes were also significantly attenuated by capsaicin pretreatment.Conclusion: Our findings suggest that capsaicin pretreatment may inhibit incision-induced keratinocytes proliferation and reduce their expression of pronociceptive inflammatory mediators under postoperative pain conditions, which represents a peripheral non-neuronal mechanism of capsaicin-induced analgesia.Keywords: capsaicin, keratinocyte, postoperative pain, inflammatory mediators